STUDI LITERATUR: PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Sepina, Imelda Azila; Kurino, Yeni Dwi; Mahpudin, Mahpudin; Rosidah, Ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creative thinking is one of the 21st-century skills that is important to develop in elementary school students. However, various findings indicate that the level of student creativity in Indonesia is still relatively low, so a learning model that can encourage active involvement and the development of creative ideas is needed. This study aims to examine the effectiveness of the Project Based Learning (PjBL) learning model on students' creative thinking skills through a literature review. The research method used is a literature review with a descriptive qualitative approach. Data were obtained from national and international scientific articles relevant to the range of PjBL topics and students' creative thinking skills, published in recent times. The results show that the implementation of the Project Based Learning model consistently has a positive and significant effect on improving students' creative thinking skills, as indicated by an increase in posttest scores, a significant difference with the control class, and indicators of creativity development such as fluency, flexibility, originality, and elaboration. In addition, PjBL also equips students with collaboration, problem-solving, and responsibility skills that are relevant to real life. Thus, the Project Based Learning model is recommended as an innovative learning alternative to improve elementary school students' creative thinking skills.